2010
DOI: 10.1016/j.compchemeng.2010.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of biofuels and biofeedstocks from aqueous solutions using ionic liquids

Abstract: The production from biomass of chemicals and fuels by fermentation, biocatalysis, and related techniques implies energy-intensive separations of organics from relatively dilute aqueous solutions, and may require use of hazardous materials as entrainers to break azeotropes.We consider the design feasibility of using ionic liquids as solvents in liquid-liquid extractions for separating organic compounds from dilute aqueous solutions. As an example, we focus on the extraction of 1-butanol from a dilute aqueous so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(52 citation statements)
references
References 36 publications
2
48
0
2
Order By: Relevance
“…Besides, ionic liquids offer the specificity required to separate similar compounds from each other (Wasserscheid & Eichmann, 2001). Several authors reported on the use of ionic liquids for extraction of biomolecules (Pei et al, 2009;Ge et al, 2010;Tomé et al, 2010), aromatic compound (Meindersma et al, 2005;Zhou et al, 2009), metals (Wei et al, 2003;Germani et al, 2007;Yoon et al, 2010;Egorov et al, 2010), and organic compounds (Marták & Schlosser, 2007;Simoni et al, 2010). The use of ionic liquids for enantioselective extraction was studied as well (Huh et al, 2006;Tang et al, 2010).…”
Section: Downstream Processing Employing Ionic Liquids Within Microflmentioning
confidence: 99%
“…Besides, ionic liquids offer the specificity required to separate similar compounds from each other (Wasserscheid & Eichmann, 2001). Several authors reported on the use of ionic liquids for extraction of biomolecules (Pei et al, 2009;Ge et al, 2010;Tomé et al, 2010), aromatic compound (Meindersma et al, 2005;Zhou et al, 2009), metals (Wei et al, 2003;Germani et al, 2007;Yoon et al, 2010;Egorov et al, 2010), and organic compounds (Marták & Schlosser, 2007;Simoni et al, 2010). The use of ionic liquids for enantioselective extraction was studied as well (Huh et al, 2006;Tang et al, 2010).…”
Section: Downstream Processing Employing Ionic Liquids Within Microflmentioning
confidence: 99%
“…1. To reduce the amounts of impurities that may be present, individual samples of ILs were dried under vacuum at 323.15 K and constantly stirred for a minimum period of 48 h. The purity of each IL was further checked by 1 H, 13 C and 19 F NMR. All samples exhibited purities according to those given by the manufacturers.…”
Section: Experimental Procedures Chemicalsmentioning
confidence: 99%
“…[2][3][4][5][6] With regard to their potential application in separation processes, there is considerable interest in replacing conventional volatile organic solvents with ILs. In particular, it has been reported that ILs have a high capacity for the separation of metal ions, 7,8 organic compounds, [9][10][11] and biofuels [12][13][14] from aqueous solution. For instance, for the latter application, Simoni et al 13 have shown that hydrophobic ILs are capable of extracting 1-butanol from aqueous solutions with a selectivity up to 300-fold.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This work represents an extension of our contribution towards the understanding of the relationship between the hydrophobic ILs chemical structures and their impact on their mutual solubilities with water [4][5][6][7][8][9][10][11][12]. Here, we focus on hydrophobic ILs, which are promising media for liquid-liquid extractions from aqueous solutions [13][14][15]. The effects of various IL structural characteristics, namely the IL anion nature [4,5], cation head group [4,6,7], cation alkyl side chain length [8], structural/ positional isomers [9,10], and fluorinated moieties [11], on their phase behaviour with water have been previously reported.…”
Section: Introductionmentioning
confidence: 99%